Lactobacillus gasseri Suppresses the Production of Proinflammatory Cytokines in Helicobacter pylori-Infected Macrophages by Inhibiting the Expression of ADAM17 - Gebremariam, Hanna G.; Qazi, Khaleda Rahman; Somiah, Tanvi; Pathak, Sushil Kumar; Sjölinder, Hong; Sverremark Ekström, Eva; Jonsson, Ann-Beth (Frontiers in Immunology, 2019)
The ability of Helicobacter pylori to evade the host immune system allows the bacterium to colonize the host for a lifetime. Long-term infection with H. pylori causes chronic inflammation, which is the major risk factor for the development of gastric ulcers and gastric cancer. Lactobacilli are part of the human microbiota and have been studied as an adjunct treatment in H. pylori eradication therapy. However, the molecular mechanisms by which lactobacilli act against H. pylori infection have not been fully characterized. In this study, we investigated the anti-inflammatory effects of Lactobacillus strains upon coincubation of host macrophages with H. pylori. We found that Lactobacillus gasseri Kx110A1 (L. gas), a strain isolated from a human stomach, but not other tested Lactobacillus species, blocked the production of the proinflammatory cytokines TNF and IL-6 in H. pylori-infected macrophages. Interestingly, L. gas also inhibited the release of these cytokines in LPS or LTA stimulated macrophages, demonstrating a general anti-inflammatory property. The inhibition of these cytokines did not occur through the polarization of macrophages from the M1 (proinflammatory) to M2 (anti-inflammatory) phenotype or through the altered viability of H. pylori or host cells. Instead, we show that L. gas suppressed the release of TNF and IL-6 by reducing the expression of ADAM17 (also known as TNF-alpha-converting enzyme, TACE) on host cells. Our findings reveal a novel mechanism by which L. gas prevents the production of the proinflammatory cytokines TNF and IL-6 in host macrophages.